2019
DOI: 10.1021/acs.iecr.9b00325
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Acidity, Defective Sites, and Diffusion Properties of Nanosheet ZSM-5 and Its Catalytic Performance in the Methanol to Propylene Reaction

Abstract: A seed-induced preparation method was developed to synthesize ZSM-5 crystals, in which two different kinds of ZSM-5 crystals were used as seeds. The different preparation methods for seeds led to the difference in the morphology and Al distribution. The results showed that the synthesized zeolites showed nanosheet morphology regardless of the types of seeds. However, the different types of seed led to the difference of synthesized zeolites in the pore structure, acid properties, and defect sites. Catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…3) showed that the prepared lamellar and nanosized samples have relatively more weak acid sites. Similar results have been reported by others confirming our findings [17,18]. The acidity results listed in Tab.…”
Section: Research Articlesupporting
confidence: 94%
See 3 more Smart Citations
“…3) showed that the prepared lamellar and nanosized samples have relatively more weak acid sites. Similar results have been reported by others confirming our findings [17,18]. The acidity results listed in Tab.…”
Section: Research Articlesupporting
confidence: 94%
“…Xing et al reported that the catalytic lifetime of sheet-like HZSM-5 zeolite is lower than that synthesized from spherical seed which is consistent with our results [18]. By increasing the crystal size of the prepared zeolites, the diffusion path reduces and the rate of secondary reactions, such as the conversion of light olefins to aromatics, increases.…”
Section: Catalytic Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…The acid sites, especially weak acid sites, were greatly related to defects. For zeolites, silicon hydroxyl, aluminum hydroxyl, and silanol nest were often referred to defective sites . The nature of hydroxyl groups was studied by FT-IR spectroscopy in Figure .…”
Section: Resultsmentioning
confidence: 99%